The Influence Of Motivation, Organization Culture, And Work Environmnet On Employee Performance - Alfiaturrohmah, Nurul; Syallsabilah, Bunga Ayu (Journal of Management and Digital Business, 2025)
Purpose – This study aims to examine how the influence of motivation, organization culture and work environment effects employee performance . Design/methodology/approach – The research uses quantitative research methods, using primary data collected from a population of 65 population working at  PT Gondowangi tradisional kosmetika. Data analysis is conducted using Patrial Least Square (PLS) software. Findings – The research reveal that motivation and work environment significantly improve employee performance. In contrast, organizational does not significantly improve employee performance. Research limitations/implications – The research is limited a particular organization, and this  can only be conducted in one sector so that the results cannot be directly applied to another sector. The research is an independent variable, employee performance as the dependent variable is meansures using a questionnaire, so the data obtained is not guided in detail in filling it out.